Composite lithium supplement agent and preparation method thereof, positive plate and lithium ion battery

By doping single-atom copper in Li5FeO4 into titanium dioxide composite material, a composite lithium supplement agent with suitable median particle size is formed, which solves the problem of poor conductivity of lithium ferrate and achieves low-cost and efficient cycle stability of lithium-ion batteries Improve and electrochemical performance with excellent results.

CN119208588APending Publication Date: 2024-12-27TIANMU LAKE INST OF ADVANCED ENERGY STORAGE TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411297999.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-18
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

Lithium ferrate (Li5FeO4) has poor conductivity, resulting in a decrease in the cycle stability of lithium-ion batteries. In addition, existing modification methods such as lithium titanate are costly and it is difficult to achieve industrial production.

Method used

The composite material with Li5FeO4 with a mass ratio of 10:0.5 to 2 and single-atom copper embedded in titanium dioxide is used as a composite lithium supplement agent. The additive is prepared by reaction between copper source, titanium source and solvent, and mixed with Li5FeO4 for heat treatment to form median particles. The composite lithium supplement agent with a diameter of 5 to 10 μm improves the conductivity and cycle stability of the battery.

Benefits of technology

It realizes the low-cost preparation of composite lithium supplement agents, improves the cycle stability and electrochemical performance of lithium-ion batteries, and has a simple process and is suitable for large-scale production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005046691800000161
    Figure BDA0005046691800000161
Patent Text Reader

Abstract

The invention relates to the technical field of lithium ion batteries, in particular to a composite lithium supplement agent and a preparation method thereof, a positive plate and a lithium ion battery. The composite lithium supplement agent comprises Li5FeO4 and an additive in a mass ratio of 10: (0.5-2), and the additive comprises a composite material formed by embedding monatomic copper into titanium dioxide. The composite lithium supplement agent is good in conductivity, the battery prepared from the composite lithium supplement agent is good in cycling stability, and the composite lithium supplement agent is low in cost.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lithium ion batteries, and in particular to a composite lithium supplement and a preparation method thereof, a positive electrode sheet and a lithium ion battery. Background Art

[0002] Cathode pre-lithiation additives mainly include binary (Li2O, Li2O2, Li2S, Li3N, etc.) and ternary (Li2NiO2, Li6CoO4, Li8ZrO6, etc.) lithium-rich materials. Compared with binary lithium-rich materials, ternary lithium-rich compounds have the advantages of being safer, more stable, and more compatible. Some lithium-rich ternary materials (such as Li2NiO2) have begun to be mass-produced and applied. Based on this, Li with similar structure x M y O z (M=Co, Mn, Fe, etc.) Lithium-rich materials have also been used in the field of cathode additives. Among them, the most representative lithium ferrate (Li5FeO4) has attracted widespread attention due to its excellent comprehensive performance. However, Li5FeO4 itself has poor conductivity, which leads to a decrease in the cycle stability of the battery.

[0003] In response to the above problems, patent CN117865226A proposes using spinel structure lithium metatitanate to coat modified Li5FeO4 to improve the electronic conductivity of Li5FeO4 and the stability of the material. However, lithium metatitanate is relatively expensive and difficult to achieve industrial production.

[0004] In view of this, the present invention is proposed. Summary of the invention

[0005] The first object of the present invention is to provide a composite lithium supplement, which has good conductivity, a battery prepared from the composite lithium supplement has good cycle stability, and the cost of the composite lithium supplement is low.

[0006] The second object of the present invention is to provide a method for preparing a composite lithium supplement, which has the advantages of simple operation, short process flow, low cost and mass production.

[0007] The third object of the present invention is to provide a positive electrode sheet whose cycle performance is significantly improved.

[0008] A fourth object of the present invention is to provide a lithium ion battery having excellent cycle performance.

[0009] In order to achieve the above-mentioned purpose of the present invention, the following technical solutions are particularly adopted:

[0010] The present invention first provides a composite lithium supplement, comprising Li5FeO4 and an additive in a mass ratio of 10:0.5-2, wherein the additive comprises a composite material of single-atom copper embedded in titanium dioxide.

[0011] Furthermore, the median particle size of the additive is 5 to 7 nm.

[0012] Furthermore, the median particle size of the composite lithium supplement is 5 to 10 μm.

[0013] Furthermore, the molar ratio of the Cu element to the Ti element in the additive is 1 to 3:10.

[0014] Furthermore, the preparation method of the additive comprises the following steps: after mixing a copper source, a titanium source and a solvent, adding an acid solution thereto and reacting, and obtaining a gel after the reaction is completed; and calcining the gel to obtain the additive.

[0015] Furthermore, the copper source includes at least one of copper nitrate, copper chloride and copper acetate.

[0016] Furthermore, the titanium source includes titanium tetraisopropoxide.

[0017] Furthermore, the molar ratio of the Cu element in the copper source to the Ti element in the titanium source is 1 to 3:10.

[0018] Furthermore, the solvent includes at least one of n-butanol, isobutanol, n-propanol, isopropanol, ethylene glycol and ethanol.

[0019] Furthermore, the acid solution includes at least one of hydrochloric acid solution, sulfuric acid solution, nitric acid solution, phosphoric acid solution, glacial acetic acid solution and citric acid solution.

[0020] Furthermore, the acid solution is added until the pH value of the mixed material is 5-7.

[0021] Furthermore, the reaction temperature is 60-80°C.

[0022] Furthermore, the reaction time is 4 to 8 hours.

[0023] Furthermore, the calcination temperature is 400-600°C.

[0024] Furthermore, the calcination time is 4 to 8 hours.

[0025] Furthermore, during the process of adding the acid solution, stirring is performed continuously at a rotation speed of 800 to 1500 rpm.

[0026] The present invention further provides a method for preparing the composite lithium supplement, comprising the following steps: mixing Li5FeO4 and an additive and then performing heat treatment.

[0027] Further, the mixing method includes grinding.

[0028] Furthermore, the grinding time is 1 to 2 hours.

[0029] Furthermore, the revolution speed of the grinding is 100 to 300 rpm.

[0030] Furthermore, the grinding rotation speed is 300-550 rpm.

[0031] Furthermore, the grinding ball-to-material ratio is 1:2-4.

[0032] Furthermore, the temperature of the heat treatment is 100-140°C.

[0033] Furthermore, the heat treatment has a holding time of 2 to 5 hours.

[0034] The present invention further provides a positive electrode sheet, comprising a current collector and a positive electrode active layer arranged on the surface of the current collector, wherein the positive electrode active layer comprises the composite lithium supplement agent.

[0035] Furthermore, the mass of the composite lithium supplement accounts for 1% to 3% of the mass of the positive electrode active layer.

[0036] Furthermore, the positive electrode material in the positive electrode active layer includes lithium iron phosphate material.

[0037] The present invention also provides a lithium ion battery, comprising the positive electrode sheet.

[0038] Compared with the prior art, the present invention has the following beneficial effects:

[0039] (1) The composite lithium supplement provided by the present invention has good conductivity, the battery prepared therefrom has good cycle stability, and the cost of the composite lithium supplement is low.

[0040] (2) The composite lithium supplement provided by the present invention has good additive uniformity and suitable particle size, which is beneficial to improving the electrochemical performance of the composite lithium supplement. DETAILED DESCRIPTION

[0041] The technical scheme of the present invention will be clearly and completely described below in conjunction with specific embodiments, but it will be appreciated by those skilled in the art that the following described embodiments are part of embodiments of the present invention, rather than all embodiments, and are only used to illustrate the present invention, and should not be considered as limiting the scope of the present invention. Based on the embodiments in the present invention, all other embodiments obtained by those of ordinary skill in the art without making creative work, all belong to the scope of protection of the present invention. If specific conditions are not indicated in the embodiments, they are carried out according to normal conditions or conditions recommended by the manufacturer. If the manufacturer is not indicated in the reagents or instruments used, they are all conventional products that can be purchased commercially.

[0042] If there is no special explanation, in the present invention, "the first aspect", "the second aspect", "the third aspect", "the fourth aspect", etc. are only used for descriptive purposes and cannot be understood as indicating or implying relative importance or quantity, nor can they be understood as implicitly indicating the importance or quantity of the indicated technical features. Moreover, "the first", "the second", "the third", "the fourth", etc. only serve the purpose of non-exhaustive enumeration and description, and it should be understood that they do not constitute a closed limitation on quantity.

[0043] If there is no special explanation, the "include" and "comprising" mentioned in the present invention represent open-ended or closed-ended expressions. For example, the "include" and "comprising" may represent that other components not listed may also be included or only the listed components may be included or only the listed components may be included.

[0044] If there is no special explanation, in the present invention, "one or more" or "at least one" refers to any one, any two or more of the listed items. Among them, "several" refers to any two or more of the listed items.

[0045] In a first aspect, the present invention provides a composite lithium supplement, which includes lithium ferrate Li5FeO4 and an additive in a mass ratio of 10:0.5 to 2. The mass ratio of lithium ferrate to the additive includes but is not limited to any point value of 10:0.5, 10:0.8, 10:1, 10:1.3, 10:1.5, 10:1.8, 10:2 or a range value between any two of them. That is, the composite lithium supplement is a composite material of additive-doped Li5FeO4, wherein the additive is uniformly dispersed.

[0046] The additive includes a composite material of single-atom copper embedded in titanium dioxide, that is, the additive includes titanium dioxide loaded with single copper atoms. By capturing single Cu atoms on Ti vacancies on the surface of TiO2, the risk of short circuit in the battery cell is reduced compared to directly adding single-element Cu.

[0047] The composite lithium supplement provided by the present invention has good electrical conductivity, provides more and smoother transmission channels for lithium ions, enables lithium ions to move between electrodes more efficiently, and thus improves the cycle stability of the battery.

[0048] In addition, the composite lithium supplement has low cost and is convenient for large-scale quantitative production and wide application.

[0049] In addition, the mass ratio of lithium ferrate and additives will affect the performance of the composite lithium supplement. The above ratio can ensure the electrochemical performance of the battery, especially the cycle stability.

[0050] In some specific embodiments, the median particle size D of the additive is 50 The particle size of the composite lithium supplement is 5-7 nm, including but not limited to any point value of 5 nm, 5.5 nm, 6 nm, 6.5 nm, and 7 nm, or any range value between two of them. The use of additives in this particle size range is beneficial to improving the conductivity of the composite lithium supplement and the cycle stability of the battery prepared therefrom.

[0051] In some specific embodiments, the median particle size of the Li5FeO4 is 5 to 10 μm, including but not limited to any point value of 5 μm, 6 μm, 7 μm, 8 μm, 9 μm, 10 μm or a range value between any two of them.

[0052] In some specific embodiments, the median particle size D of the composite lithium supplement is 50 It is 5 to 10 μm, including but not limited to any point value of 5 μm, 6 μm, 7 μm, 8 μm, 9 μm, and 10 μm, or a range value between any two of them.

[0053] In some specific embodiments, the molar ratio of Cu element to Ti element in the additive is 1 to 3:10, including but not limited to any point value of 1:10, 1.2:10, 1.5:10, 1.8:10, 2:10, 2.3:10, 2.5:10, 2.7:10, 3:10 or any range value between two of them. Controlling the Cu element and the Ti element within the above ratio range can further improve the conductivity of the composite lithium supplement and the electrochemical performance of the battery prepared therefrom.

[0054] In some specific embodiments, the preparation method of the additive comprises the following steps: after the copper source, the titanium source and the solvent are uniformly mixed, an acid solution is added thereto, and the mixture is reacted to obtain a gel after the reaction is completed. The gel is calcined and cooled to obtain the additive.

[0055] The additive prepared by the above method has good uniformity and suitable particle size, which is beneficial to improving the conductivity of the composite lithium supplement.

[0056] In some specific embodiments, the copper source includes at least one of copper nitrate, copper chloride and copper acetate, or two or three of them may be selected.

[0057] It is understandable that the copper source may be a compound with or without water of crystallization, and the present invention does not limit this.

[0058] In some specific embodiments, the titanium source includes titanium tetraisopropoxide.

[0059] In some specific embodiments, the molar ratio of the Cu element in the copper source to the Ti element in the titanium source is 1 to 3:10, including but not limited to any point value of 1:10, 1.2:10, 1.5:10, 1.8:10, 2:10, 2.3:10, 2.5:10, 2.7:10, 2.8:10, 3:10 or a range value between any two of them.

[0060] In some specific embodiments, the solvent includes at least one of n-butanol, isobutanol, n-propanol, isopropanol, ethylene glycol and ethanol, and preferably two or more of them are used, which is beneficial to improve the uniformity of the prepared additive.

[0061] In some specific embodiments, the acid solution includes at least one of hydrochloric acid solution, sulfuric acid solution, nitric acid solution, phosphoric acid solution, glacial acetic acid solution and citric acid solution, or two or three of them may be selected.

[0062] In some specific embodiments, the pH value of the acid solution added to the mixed material is 5-7, that is, the amount of the acid solution added is adjusted to a pH value of the system of 5-7, including but not limited to any point value of 5, 5.3, 5.5, 5.8, 6, 6.2, 6.5, 6.7, 7 or a range value between any two of them.

[0063] In some specific embodiments, the reaction temperature is 60-80°C, including but not limited to any one of 60°C, 65°C, 70°C, 75°C, 80°C or a range between any two of them.

[0064] In some specific embodiments, the reaction time is 4 to 8 hours, including but not limited to any one of 4h, 5h, 6h, 8h, 10h, 12h, 13h, 15h, 18h, 20h, 22h, and 24h, or a range between any two of them.

[0065] In some specific embodiments, the calcination temperature is 400-600°C, including but not limited to any one of 400°C, 450°C, 500°C, 550°C, 600°C or a range between any two of them; the calcination time is 4-8h, including but not limited to any one of 4h, 5h, 6h, 7h, 8h or a range between any two of them.

[0066] In some specific embodiments, the acid solution is added with continuous stirring.

[0067] In some specific implementations, the stirring time is 30 to 120 min, such as 60 min or 90 min.

[0068] In some specific embodiments, the stirring speed is 800-1500 rpm, including but not limited to any one of 800 rpm, 900 rpm, 1000 rpm, 1200 rpm, 1300 rpm, and 1500 rpm or any range between two thereof. High-speed stirring is beneficial to improving the uniformity of the copper element dispersion in the prepared additive, thereby improving the performance of the additive.

[0069] The use of the above-mentioned preparation parameters can effectively capture Cu single atoms on the Ti vacancies on the TiO2 surface, and is beneficial to improving the uniformity of Cu single atom dispersion, thereby improving the performance of the composite lithium supplement.

[0070] Lithium ferrate can easily cause gas production in batteries. The composite lithium supplement provided by the present invention can also inhibit gas production in batteries and avoid battery bulging problems.

[0071] In some specific embodiments, the calcination atmosphere includes air atmosphere and / or oxygen atmosphere.

[0072] In some specific embodiments, the median particle size D of the additive prepared by the above method is 50 It is 5 to 7 nm, including but not limited to any point value of 5 nm, 5.5 nm, 6 nm, 6.5 nm, and 7 nm, or a range value between any two of them.

[0073] In a second aspect, the present invention provides a method for preparing the composite lithium supplement, comprising the following steps: mixing Li5FeO4 and an additive uniformly, performing heat treatment, and cooling to obtain the composite lithium supplement.

[0074] The preparation method has the advantages of simple operation, short process, low cost, and suitability for mass production.

[0075] In addition, the composite lithium supplement prepared by the above method has excellent electrochemical performance.

[0076] In some specific embodiments, the mixing method includes grinding. Grinding can make the raw materials disperse more evenly, thereby improving the uniformity of the composite lithium supplement.

[0077] In some specific embodiments, the grinding time is 1 to 2 hours (1.5 hours can also be selected), the revolution speed of the grinding is 100 to 300 rpm (150 rpm, 200 rpm or 250 rpm can also be selected), the rotation speed of the grinding is 300 to 550 rpm (350 rpm, 400 rpm, 450 rpm or 500 rpm can also be selected), and the ball-to-material ratio of the grinding is 1:2 to 4 (1:3 can also be selected).

[0078] In some specific embodiments, the heat treatment temperature is 100-140°C, including but not limited to any one of 100°C, 110°C, 120°C, 130°C, 140°C or any range between two thereof. The heat treatment can improve the crystallinity of the composite lithium supplement and remove moisture.

[0079] In some specific embodiments, the heat treatment holding time is 2 to 5 hours, including but not limited to any one of 2 hours, 3 hours, 4 hours, and 5 hours or a range between any two of them.

[0080] In some specific embodiments, the heat treatment is performed under vacuum.

[0081] In a third aspect, the present invention provides a positive electrode sheet, comprising a current collector and a positive electrode active layer disposed on the surface of the current collector, wherein the positive electrode active layer comprises the above-mentioned composite lithium supplement.

[0082] The positive electrode sheet has excellent electrochemical performance, especially the cycle performance is significantly improved.

[0083] In some specific embodiments, the mass of the composite lithium supplementer accounts for 1% to 3% of the mass of the positive electrode active layer; including but not limited to any point value of 1%, 1.5%, 2%, 2.5%, 3% or any range value between the two. The amount of composite lithium supplementer added will affect the performance of the battery. The above ratio is conducive to improving the electrochemical performance of the battery, especially the cycle performance.

[0084] In some specific embodiments, the positive electrode material in the positive electrode active layer includes a lithium iron phosphate material, wherein the lithium iron phosphate material includes at least one of lithium iron phosphate doped with metal or non-metal, undoped lithium iron phosphate, lithium iron phosphate with a coating layer, and lithium iron phosphate without a coating layer.

[0085] As the lithium iron phosphate positive electrode material is used in cycles, lithium ions will be continuously embedded and extracted between the positive and negative electrodes, resulting in a gradual reduction in active lithium. The composite lithium supplement provided by the present invention can continuously provide lithium ions during the battery cycle, increase the active lithium content in the battery, and thus maintain the capacity of the battery. Therefore, the use of the composite lithium supplement provided by the present invention in combination with the lithium iron phosphate positive electrode material can improve the electrochemical performance of the battery, with a synergistic effect.

[0086] Optionally, the positive electrode active layer further includes a binder and / or a conductive agent.

[0087] Specifically, the adhesive may be any material with adhesive properties commonly used in the art, such as polyvinylidene fluoride (PVDF), but is not limited thereto.

[0088] The conductive agent may also be any conductive material commonly used in the art, such as carbon black, graphite, conductive polymer, etc., but is not limited thereto.

[0089] In some specific embodiments, the preparation method of the positive electrode sheet includes: mixing the positive electrode material, the composite lithium supplement agent, the conductive agent, the binder and the solvent evenly to obtain a positive electrode slurry, and coating (applying) it to the surface of the current collector, and obtaining the positive electrode sheet after drying.

[0090] In a fourth aspect, the present invention provides a lithium-ion battery, comprising the positive electrode sheet.

[0091] The lithium-ion battery has good electrochemical performance, especially excellent cycle performance.

[0092] Optionally, the lithium-ion battery further comprises a negative electrode sheet, a separator and an electrolyte, which is not limited in the present invention, and the negative electrode sheet, separator and electrolyte known to those skilled in the art may be used.

[0093] In some specific implementations, the coated positive electrode sheet is first rolled, then die-cut, and then stacked, baked, injected, packaged, aged, formed, and divided into volumes to obtain a 065085 soft-pack battery cell.

[0094] The embodiments of the present invention will be described in detail below in conjunction with the examples, but it will be appreciated by those skilled in the art that the following examples are only used to illustrate the present invention and should not be considered as limiting the scope of the present invention. If no specific conditions are specified in the examples, the conditions are carried out according to normal conditions or the conditions recommended by the manufacturer. If the manufacturer is not specified for the reagents or instruments used, they are all conventional products that can be obtained commercially.

[0095] Example 1

[0096] The preparation method of the composite lithium supplement provided in this embodiment comprises the following steps:

[0097] (1) Preparation of additive, i.e., composite material of single-atom copper embedded in titanium dioxide: copper source Cu(NO3)2·3H2O, titanium source titanium tetraisopropoxide, and solvent n-butanol and ethylene glycol (volume ratio of n-butanol and ethylene glycol is 1:1) were added to a 150 mL beaker, and stirred to obtain a mixed solution, wherein the molar ratio of Cu element to Ti element was 1:10. Nitric acid solution was added to the mixed solution until the pH value of the mixed solution reached 6, and the mixture was stirred continuously at a speed of 1100 rpm. After stirring for 30 min, the mixture was reacted at a temperature of 70°C for 4 h to obtain a clear bright blue gel. The gel was calcined in an air furnace at 450°C for 4 h (air atmosphere), and the additive was obtained after cooling. The additive is a composite material of single-atom copper embedded in titanium dioxide, wherein the median particle size is 6.1 nm, and the molar ratio of Cu element to Ti element in the additive is 1:10.

[0098] (2) The Li5FeO4 powder with a median particle size of 8 μm and the additive obtained in step (1) are mixed and ground in a mass ratio of 10:1, the revolution speed of the grinding is 200 rpm, the rotation speed is 400 rpm, the grinding ball-to-material ratio is 1:3, and the grinding time is 2 hours. After the grinding is completed, the mixed powder is transferred to an aluminum-plastic film bag and heat-treated in a vacuum oven at 120° C. for 2 hours (vacuum conditions) to obtain a composite lithium supplement, that is, a composite material doped with Li5FeO4, wherein the median particle size is 8.3 μm.

[0099] The positive electrode sheet provided in this embodiment includes a current collector and a positive electrode active layer disposed on the surface of the current collector, and the positive electrode active layer includes the following components by mass percentage: 94.66% lithium iron phosphate, 1.94% of the composite lithium supplement prepared in this embodiment 1, 0.7% of conductive carbon black, 0.3% of CNT conductive slurry (which consists of CNT and NMP, with a solid content of 4%), 0.2% of dispersant acrylate, and 2.2% of PVDF. That is, the mass of the composite lithium supplement accounts for 1.94% of the mass of the positive electrode active layer.

[0100] The preparation method of the positive electrode sheet is as follows: according to the above formula, each material is mixed evenly, and then NMP solvent is added, and the mixture is stirred into a slurry in a vacuum mixer to obtain a positive electrode slurry, and the positive electrode slurry is evenly coated on an aluminum foil using a coating machine and dried, and the coating surface density is 380g / m 2 The preparation method of the negative electrode sheet is as follows: weigh each material according to the mass ratio of graphite: conductive carbon black: CMC: SBR = 96.3: 0.5: 1.4: 1.8, add NMP solvent, and then stir into a slurry in a vacuum mixer to obtain a negative electrode slurry, and use a coating machine to evenly coat the negative electrode slurry on a copper foil and dry it. The coating surface density is 172g / m 2, and then roll-pressed to obtain the negative electrode sheet. The electrolyte is a mixed solution of LiPF6 (concentration of 1.3 mol / L), and the solvent is EC, EMC and DMC in a mass ratio of 25:5:70. The diaphragm is a 12μm PP (polypropylene) diaphragm. The above-mentioned positive electrode sheet, negative electrode sheet, diaphragm and electrolyte are assembled, and after lamination, baking, injection, packaging, aging, formation and volume separation, a 700mAh 065085 soft-pack battery cell is obtained.

[0101] Example 2

[0102] The preparation method of the composite lithium supplement provided in this embodiment is basically the same as that in Embodiment 1, except that in step (2), the mass ratio of Li5FeO4 to the additive is 10:0.5.

[0103] The composite lithium supplement agent prepared in this example was used to prepare a positive electrode sheet according to the ratio and method of Example 1, and the positive electrode sheet was assembled into a 700mAh 065085 soft-pack battery cell.

[0104] Example 3

[0105] The preparation method of the composite lithium supplement provided in this embodiment is basically the same as that in Embodiment 1, except that in step (2), the mass ratio of Li5FeO4 to the additive is 10:1.5.

[0106] The composite lithium supplement agent prepared in this example was used to prepare a positive electrode sheet according to the ratio and method of Example 1, and the positive electrode sheet was assembled into a 700mAh 065085 soft-pack battery cell.

[0107] Example 4

[0108] The preparation method of the composite lithium supplement provided in this embodiment is basically the same as that in Example 1, except that in step (1), Cu(NO3)2·3H2O and titanium tetraisopropoxide are added according to a molar ratio of Cu element to Ti element of 2:10.

[0109] The composite lithium supplement agent prepared in this example was used to prepare a positive electrode sheet according to the ratio and method of Example 1, and the positive electrode sheet was assembled into a 700mAh 065085 soft-pack battery cell.

[0110] Example 5

[0111] The preparation method of the composite lithium supplement provided in this embodiment is basically the same as that in Example 1, except that in step (1), Cu(NO3)2·3H2O and titanium tetraisopropoxide are added according to a molar ratio of Cu element to Ti element of 3:10.

[0112] The composite lithium supplement agent prepared in this example was used to prepare a positive electrode sheet according to the ratio and method of Example 1, and the positive electrode sheet was assembled into a 700mAh 065085 soft-pack battery cell.

[0113] Example 6

[0114] The preparation method of the composite lithium supplement provided in this embodiment comprises the following steps:

[0115] (1) Preparation of additive, i.e., composite material of single-atom copper embedded in titanium dioxide: add copper acetate, titanium source tetraisopropoxide titanium and solvent n-propanol and ethanol (volume ratio of the two is 1:1) into a 150mL beaker, stir evenly to obtain a mixed solution, wherein the molar ratio of Cu element to Ti element is 1.2:10. Add acetic acid solution to the mixed solution until the pH value of the mixed solution is 5.5, stir continuously at a speed of 1300rpm, stir for 30min, react at 80℃ for 6h, and obtain a clear bright blue gel. Calcine the gel in an air furnace at 550℃ for 6h (air atmosphere), and obtain the additive after cooling. The additive is a composite material of single-atom copper embedded in titanium dioxide, wherein the median particle size is 5.4nm, and the molar ratio of Cu element to Ti element in the additive is 1.2:10.

[0116] (2) The Li5FeO4 powder with a median particle size of 6 μm and the additive obtained in step (1) were mixed and ground in a mass ratio of 10:1.3, with a revolution speed of 300 rpm, a rotation speed of 400 rpm, a ball-to-material ratio of 1:2, and a grinding time of 1 h. After grinding, the mixed powder was transferred to an aluminum-plastic film bag and heat-treated in a vacuum oven at 140° C. for 3 h to obtain a composite lithium supplement, i.e., a composite material doped with additive-doped Li5FeO4, with a median particle size of 6.1 μm.

[0117] The composite lithium supplement agent prepared in this example was used to prepare a positive electrode sheet according to the ratio and method of Example 1, and the positive electrode sheet was assembled into a 700mAh 065085 soft-pack battery cell.

[0118] Example 7

[0119] The composite lithium supplement agent prepared in Example 1 was used to prepare a positive electrode sheet substantially according to the ratio and method of Example 1, and the positive electrode sheet was assembled into a 700mAh 065085 soft-pack battery cell, except that the mass percentage of lithium iron phosphate was replaced with 95.6%, and the mass percentage of the composite lithium supplement agent was replaced with 1%.

[0120] Comparative Example 1

[0121] The lithium supplement provided in this comparative example is Li5FeO4 with a median particle size of 8 μm.

[0122] The lithium supplement agent of this comparative example was used to prepare a positive electrode sheet according to the ratio and method of Example 1, and the positive electrode sheet was assembled into a 700mAh 065085 soft-pack battery cell.

[0123] Comparative Example 2

[0124] The preparation method of the lithium supplement provided in this comparative example is basically the same as that of Example 1, except that in step (1), no copper source Cu(NO3)2·3H2O is added.

[0125] The lithium supplement agent prepared in this comparative example was used to prepare a positive electrode sheet according to the ratio and method of Example 1, and the positive electrode sheet was assembled into a 700mAh 065085 soft-pack battery cell.

[0126] Comparative Example 3

[0127] The preparation method of the lithium supplement provided in this comparative example is basically the same as that of Example 1, except that in step (1), titanium tetraisopropoxide, a titanium source, is not added.

[0128] The lithium supplement agent prepared in this comparative example was used to prepare a positive electrode sheet according to the ratio and method of Example 1, and the positive electrode sheet was assembled into a 700mAh 065085 soft-pack battery cell.

[0129] Comparative Example 4

[0130] The preparation method of the lithium supplement provided in this comparative example is basically the same as that of Example 1, except that in step (1), no copper source Cu(NO3)2·3H2O is added, but in step (2), an equimolar amount of copper oxide is added when mixing and grinding with Li5FeO4 based on the copper element.

[0131] The lithium supplement agent prepared in this comparative example was used to prepare a positive electrode sheet according to the ratio and method of Example 1, and the positive electrode sheet was assembled into a 700mAh 065085 soft-pack battery cell.

[0132] Comparative Example 5

[0133] The preparation method of the lithium supplement provided in this comparative example is basically the same as that of Example 1, except that in step (1), no copper source Cu(NO3)2·3H2O is added, but in step (2), an equimolar amount of cuprous oxide is added when mixing and grinding with Li5FeO4 based on the copper element.

[0134] The lithium supplement agent prepared in this comparative example was used to prepare a positive electrode sheet according to the ratio and method of Example 1, and the positive electrode sheet was assembled into a 700mAh 065085 soft-pack battery cell.

[0135] Comparative Example 6

[0136] The preparation method of the lithium supplement provided in this comparative example is basically the same as that of Example 1, except that in step (1), no copper source Cu(NO3)2·3H2O is added, but in step (2), an equimolar amount of elemental copper is added when mixing and grinding with Li5FeO4.

[0137] The lithium supplement agent prepared in this comparative example was used to prepare a positive electrode sheet according to the ratio and method of Example 1, and the positive electrode sheet was assembled into a 700mAh 065085 soft-pack battery cell.

[0138] Comparative Example 7

[0139] The preparation method of the lithium supplement provided in this comparative example is basically the same as that of Example 1, except that in step (1), titanium source tetraisopropoxide titanium is not added, but titanium dioxide is added in an equal molar amount based on the titanium element when mixing and grinding with Li5FeO4 in step (2).

[0140] The lithium supplement agent prepared in this comparative example was used to prepare a positive electrode sheet according to the ratio and method of Example 1, and the positive electrode sheet was assembled into a 700mAh 065085 soft-pack battery cell.

[0141] Comparative Example 8

[0142] The preparation method of the lithium supplement provided in this comparative example is basically the same as that of Example 1, except that in step (1), Cu(NO3)2·3H2O and titanium tetraisopropoxide are added according to a molar ratio of Cu element to Ti element of 1:20.

[0143] The lithium supplement agent prepared in this comparative example was used to prepare a positive electrode sheet according to the ratio and method of Example 1, and the positive electrode sheet was assembled into a 700mAh 065085 soft-pack battery cell.

[0144] Comparative Example 9

[0145] The preparation method of the lithium supplement agent provided in this comparative example is basically the same as that of Example 1, except that in step (2), the mass ratio of Li5FeO4 to the additive is 10:5.

[0146] The lithium supplement agent prepared in this comparative example was used to prepare a positive electrode sheet according to the ratio and method of Example 1, and the positive electrode sheet was assembled into a 700mAh 065085 soft-pack battery cell.

[0147] Comparative Example 10

[0148] The composite lithium supplement agent prepared in Example 1 was used to prepare a positive electrode sheet substantially according to the ratio and method of Example 1, and the positive electrode sheet was assembled into a 700mAh 065085 soft-pack battery cell, except that the mass percentage of lithium iron phosphate was replaced with 96.1%, and the mass percentage of the composite lithium supplement agent was replaced with 0.5%.

[0149] Experimental example

[0150] The conductivity test was performed on the composite lithium supplement agent prepared in each embodiment and the lithium supplement agent prepared in each comparative example, and the results are shown in Table 1.

[0151] The electrochemical performance of the batteries prepared in each embodiment and each comparative example was tested, and the results are shown in Table 1.

[0152] Among them, the formation steps of the battery cell are: charge at 0.035A cross current for 60 minutes, stand for 1 minute, then charge at 0.07A constant current for 60 minutes, stand for 1 minute, and continue to charge at 0.07A constant current and constant voltage to 4.2V, with a cut-off current of 0.035A.

[0153] The test method for cycle performance is as follows: before the test, install the test fixture on the soft pack battery cell, charge the battery to 3.65V at a constant current of 0.35A in a 45℃ oven, then switch to constant voltage charging to 0.035A cutoff, leave for 30 minutes, discharge to 2.5V at a constant current of 0.7A, leave for 30 minutes, and record the discharge capacity as C1. Repeat the first two test steps, and the discharge capacity is recorded as C n (n is the number of cycles), capacity retention rate = C n / C1×100%.

[0154] First discharge gram capacity = first 0.2C discharge capacity / mass of active material (the sum of the mass of lithium iron phosphate and composite lithium supplement).

[0155] First coulombic efficiency = first 0.2C discharge capacity / formation charge capacity.

[0156] In addition, the volume change before and after formation is tested by the isobaric method (Archimedes drainage method): the soft-pack battery cell is suspended on a fixed bracket and completely immersed in a constant temperature liquid, and then the entire liquid container is placed on a weighing sensor; the masses before and after formation are recorded as m1 and m2 respectively, and the volume change is ΔV = (m1-m2) / ρ 水 The test results are shown in Table 1.

[0157] Table 1 Electrochemical performance test results

[0158]

[0159] It can be seen from Table 1 that, compared with the comparative examples, the composite lithium supplement prepared in each embodiment has a higher conductivity, and the battery assembled in each embodiment has a better cycle performance and a higher capacity.

[0160] Specifically, by comparing Example 1 and Comparative Example 1, it can be seen that the cyclic performance of Example 1 containing the additive of single-atom copper embedded in titanium dioxide is significantly improved compared with the undoped additive in Comparative Example 1.

[0161] It can be seen that in the composite lithium supplement provided by the present invention, the incorporated Cu single atom is effectively captured on the Ti vacancy on the TiO2 surface, which will not cause the short circuit and self-discharge in the battery cell, and the Cu single atom forms a conductive network or increases the electron transmission channel in Li5FeO4, thereby improving the overall conductivity of the composite lithium supplement, which helps to reduce the internal resistance of the battery and improve the capacity and cycle stability of the battery.

[0162] In addition, although Comparative Examples 2 to 7 contain copper or titanium, the cycle performance is still reduced because a composite material of single-atom copper embedded in titanium dioxide is not formed.

[0163] In Comparative Example 8, the molar ratio of copper to titanium elements is not suitable, resulting in decreased cycle performance.

[0164] In Comparative Example 9, the mass ratio of Li5FeO4 to the additive is not appropriate, resulting in a decrease in the cycle performance.

[0165] The mass fraction of the composite lithium supplement in the positive electrode sheet of Comparative Example 10 is relatively low, resulting in a decrease in cycle performance.

[0166] This shows that the specific form of additives, that is, the composite material of single-atom copper embedded in titanium dioxide, and the ratio of the composite lithium supplement also have a certain influence on the cycle performance of the battery. At the same time, the amount of the composite lithium supplement also has a certain influence on the cycle performance of the battery.

[0167] In addition, the volume change of the battery cells of each embodiment before and after formation is small. This is because the additive catalyzes the reaction of CO and active oxygen to form CO2, and at the same time, the chemically adsorbed oxygen further replenishes the active oxygen, removing the non-reactive gas oxygen and carbon monoxide in the battery to generate carbon dioxide. The carbon dioxide can be absorbed by the graphite negative electrode, thereby reducing the overall gas production of the battery.

[0168] Although the present invention has been illustrated and described with specific embodiments, it should be appreciated that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Those skilled in the art should understand that the technical solutions described in the above embodiments may be modified, or some or all of the technical features thereof may be replaced by equivalents without departing from the spirit and scope of the present invention. However, these modifications or replacements do not make the essence of the corresponding technical solutions deviate from the scope of the technical solutions of the embodiments of the present invention. Therefore, this means that all such replacements and modifications within the scope of the present invention are included in the appended claims.

Claims

1. A composite lithium supplement, characterized in that: The invention comprises Li5FeO4 and an additive in a mass ratio of 10:0.5-2, wherein the additive comprises a composite material in which single-atom copper is embedded in titanium dioxide.

2. The composite lithium supplement according to claim 1, characterized in that: The median particle size of the additive is 5 to 7 nm; And / or, the median particle size of the composite lithium supplement is 5 to 10 μm.

3. The composite lithium supplement according to claim 1, characterized in that: The molar ratio of the Cu element to the Ti element in the additive is 1 to 3:

10.

4. The composite lithium supplement according to claim 1, characterized in that: The preparation method of the additive comprises the following steps: mixing a copper source, a titanium source and a solvent, adding an acid solution thereto, and reacting to obtain a gel after the reaction is completed; and calcining the gel to obtain the additive.

5. The composite lithium supplement according to claim 4, characterized in that: At least one of the following conditions is met: (1) The copper source includes at least one of copper nitrate, copper chloride and copper acetate; (2) The titanium source includes titanium tetraisopropoxide; (3) The molar ratio of the Cu element in the copper source to the Ti element in the titanium source is 1 to 3:10; (4) The solvent comprises at least one of n-butanol, isobutanol, n-propanol, isopropanol, ethylene glycol and ethanol; (5) The acid solution includes at least one of hydrochloric acid solution, sulfuric acid solution, nitric acid solution, phosphoric acid solution, glacial acetic acid solution and citric acid solution; (6) adding the acid solution until the pH value of the mixed material reaches 5 to 7; (7) The reaction temperature is 60 to 80°C; (8) The reaction time is 4 to 8 hours; (9) The calcination temperature is 400-600° C. and the calcination time is 4-8 hours; (10) During the process of adding the acid solution, stirring is continued at a speed of 800 to 1500 rpm.

6. The method for preparing the composite lithium supplement according to any one of claims 1 to 5, characterized in that: The method comprises the following steps: mixing Li5FeO4 and additives and then performing heat treatment.

7. The method for preparing the composite lithium supplement according to claim 6, characterized in that: At least one of the following conditions is met: (1) The mixing method includes grinding, the grinding time is 1 to 2 hours, the revolution speed of the grinding is 100 to 300 rpm, the rotation speed of the grinding is 300 to 550 rpm, and the ball-to-material ratio of the grinding is 1:2 to 4; (2) The temperature of the heat treatment is 100 to 140° C.; (3) The heat treatment holding time is 2 to 5 hours.

8. A positive electrode sheet, characterized in that: The invention comprises a current collector and a positive electrode active layer arranged on the surface of the current collector, wherein the positive electrode active layer comprises the composite lithium supplement agent according to any one of claims 1 to 5.

9. The positive electrode sheet according to claim 8, characterized in that: At least one of the following conditions is met: (1) The mass percentage of the composite lithium supplement agent to the mass percentage of the positive electrode active layer is 1% to 3%; (2) The positive electrode material in the positive electrode active layer includes lithium iron phosphate material.

10. A lithium ion battery, characterized in that: Comprising the positive electrode sheet as claimed in claim 8.